Developing Waqf-Based Models for Affordable Urban Housing: Solutions for Indonesia - Mir’atun Nisa; Raditya Sukmana (Badan Wakaf Indonesia, 2026)
Affordable housing crisis in urban areas in Indonesia has become an unresolved structural issue, particularly for low-income and socially vulnerable groups. Amidst the high market value of residential land in urban areas and the increasing dominance of foreign ownership of strategic land, waqf, as an Islamic financial instrument and social asset, offers a relevant and equitable alternative approach. This research explores the potential for optimizing waqf land, which has been underutilized productively, to develop it as a model for providing housing in urban areas. The model proposed in this research utilizes a waqf-based vertical housing development scheme with feasible financing sources such as CWLS, social grants, to CSR. Residents are also provided with a series of social development and economic empowerment programs supported by other social instruments such as Zakat (if eligible), Infaq, and Sadaqah (charity), so that housing becomes a space for growth, not just a place to live. Using qualitative methods through literature reviews and in-depth interviews with relevant experts, the findings of this study emphasize the importance of a vertical approach in maximizing the efficiency of urban waqf land, while simultaneously addressing the urgency of providing inclusive and sustainable housing. Successful practices of vertical housing in various countries are also included, challenging full private ownership as a necessary condition for residential stability. Furthermore, various determining factors for the success of this model, including location, management, ownership structure, and multi-stakeholder involvement in its management, are also explained as considerations for its implementation.